Analysis of the Inheritance Rights of Adopted Children with Disabilities - Muhamad Jamal; Ali Mustofa; Nashih Muhammad (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study examines the inheritance rights of adopted children with disabilities from the perspective of maqashid shari’ah, using a case study in Prampelan Hamlet, Adipuro Village, Kaliangkrik District, Magelang Regency. In Islamic law, adopted children lack a blood relationship (nasab) with their adoptive parents and are therefore not automatically entitled to inherit. However, in the research area, adopted children—particularly those who are the only dependents and have disabilities—are often treated as biological children, including in inheritance matters. A descriptive qualitative approach was employed, with data collected through observation, interviews, and document analysis. The findings indicate that inheritance practices for adopted children with disabilities are primarily motivated by compassion and social responsibility rather than strict legal norms. Although these practices do not fully conform to formal Islamic inheritance law, they reflect the objectives of maqashid shari’ah, especially in the principles of hifz al-nafs (protection of life) and hifz al-mal (protection of wealth), providing social protection for vulnerable groups. The study recommends enhancing public understanding of Islamic inheritance law and utilizing Islamic legal mechanisms such as wasiat wajibah (mandatory bequests), hibah (gifts), and waqf (endowment) to ensure justice and legal protection for adopted children with disabilities.